Economic Feasibility of Cooling Dry Cows: Findings and Spreadsheet: AN342, 3/2018 - Ferreira, Fernanda; Dahl, Geoffrey E.; De Vries, Albert (EDIS, 2018)
The negative effects of heat stress in lactating cows are well known, but only recent studies have explored those effects along with the full benefits of cooling dry cows. Recent work at the University of Florida has demonstrated the benefits of dry cow cooling on calf performance and cow health in the next lactation. This 5-page fact sheet discusses the economic losses from milk production due to heat stress, investment, utilities, maintenance, and feasibility analysis. Written by Fernanda Ferreira, Geoffrey Dahl, and Albert De Vries, and published by the UF/IFAS Department of Animal Sciences, March 2018. http://edis.ifas.ufl.edu/an342